THE DISRUPTION OF HOME AND IDENTITY IN BLACK BRITISH WRITING - Lilyana, Sandra (Kajian Linguistik dan Sastra, 2007)
As people of the diaspora, most Black British writers have long been troubledand fascinated by the ideas of âhomeâ and âidentity.â A lot of their works present asense of not belonging anywhere and a quest for a new kind of identity not limitedto national boundaries. Such issues are portrayed most clearly in Buchi Emechetaâsnovel, Kehinde, where the protagonistâs conception of âhomeâ and âidentityâ is disruptedbetween Nigerian and British and how she ends up creating a new and morefluid identity for herself.